Dementia and Diet, Methodological and Statistical Issues: A Pilot Study - Stecker, Mark; Stecker, Mona; Reiss, Allison B.; Kasselman, Lora (Frontiers in Aging Neuroscience, 2022)
There is conflicting information on the relationship between diet and dementia. The purposes of this pilot study were twofold. First, to use publicly available data regarding food consumption (United Kingdom Family Food), dementia, risk and demographic factors to find relationships between the consumption of various foods to dementia prevalence. The second purpose was to identify elements of study design that had important effects on the results. Multiple analyses were performed on different data sets derived from the existing data. Statistical testing began with univariate correlation analyses corrected for multiple testing followed by global tests for significance. Subsequently, a number of multivariate techniques were applied including stepwise linear regression, cluster regression, regularized regression, and principal components analysis. Permutation tests and simulations highlighted the strength and weakness of each technique. The univariate analyses demonstrated that the consumption of certain foods was highly associated with the prevalence of dementia. However, because of the complexity of the data set and the high degree of correlation between variables, different multivariate analyses yielded different results, explainable by the correlations. Some factors identified as having potential associations were the consumption of rice, sugar, fruit, potatoes, meat products and fish. However, within a given dietary category there were often a number of different elements with different relations to dementia. This pilot study demonstrates some critical elements for a future study: (1) dietary factors must be very narrowly defined, (2) large numbers of cases are needed to support multivariable analyses. (3) Multiple statistical methods along with simulations must be used to confirm results.